Evaluation of Clinical Methods for Peroneal Muscle Testing. (22nd August 2012) - Sarig‐Bahat, Hilla; Krasovsky, Andrei; Sprecher, Elliot
Abstract Background Manual muscle testing of the peroneal muscles is well accepted as a testing method in musculoskeletal physiotherapy for the assessment of the foot and ankle. The peroneus longus and brevis are primary evertors and secondary plantar flexors of the ankle joint. However, some international textbooks describe them as dorsi flexors, when instructing peroneal muscle testing. The identified variability raised a question whether these educational texts are reflected in the clinical field. Purpose The purposes of this study were to investigate what are the methods commonly used in the clinical field for peroneal muscle testing and to evaluate their compatibility with functional anatomy. Methods A cross‐sectional study was conducted, using an electronic questionnaire sent to 143 Israeli physiotherapists in the musculoskeletal field. The survey questioned on the anatomical location of manual resistance and the combination of motions resisted. Results Ninety‐seven responses were received. The majority (69%) of respondents related correctly to the peronei as evertors, but asserted that resistance should be located over the dorsal aspect of the fifth metatarsus, thereby disregarding the peroneus longus. Moreover, 38% of the respondents described the peronei as dorsi flexors, rather than plantar flexors. Only 2% selected the correct method of resisting plantarflexion and eversion at the base of the first metatarsus. We consider this technique to be the most compatible with the anatomy of the peroneus longus and brevis. The Fisher–Freeman–Halton test indicated that there was a significant relationship between responses on the questions (P = 0.0253, 95% CI 0.0249–0.0257), thus justifying further correspondence analysis. The correspondence analysis found no clustering of the answers that were compatible with anatomical evidence and were applied in the correct technique, but did demonstrate a common error, resisting dorsiflexion rather than plantarflexion, which was in agreement with the described frequencies. Conclusion Inconsistencies were identified between the instruction method commonly provided for peroneal muscle testing in textbook and the functional anatomy of these muscles. Results reflect the lack of accuracy in applying functional anatomy to peroneal testing. This may be due to limited use of peroneal muscle testing or to inadequate investigation of the existing evaluation methods and their validity. Accordingly, teaching materials and clinical methods used for this test should be re‐evaluated. Further research should investigate the value of peroneal muscle testing in clinical ankle evaluation. Copyright © 2012 John Wiley & Sons, Ltd.